Electronic HRM in the smart era - Bondarouk, Tanya, 1967-; Ruel, Huub; Parry, Emma (The changing context of managing people, 2017)
The HRM field is entering smart businesses where the human,digital and high-tech dimensions seem to increasingly converge, and HRM needsto anticipate its own "smart" future. Technological developments andinterconnectedness with and through the Internet (often called the "Internet of Things") set new challenges for the HRM function. Smartness enacted by HRMprofessionals - notions of "smart industries", "smart things" and "smartservices" all put new pressures on strategic HRM. Since the 1990s,organisations have increasingly been introducing electronic Human ResourceManagement (e-HRM), with the expectation of improving the quality of HRM andincreasing its contribution to firm performance. These beliefs originate fromideas about the endless possibilities of information technologies (IT) infacilitating HR practices, and about the infinite capacity of HRM to adopt IT.This book focuses on the progression from e-HRM to digital HRM towards smart HRM. It also raises several important questions that businessesand scholars are confronted with: What kind of smart solution can and will HRM offer to meet the expectations of thelatest business developments? Can HRM become "smart" and combinedigitisation, automation and a network approach? How do businesses futureprooftheir HRM in the smart era? What competences do employees need to ensurebusinesses flourish in smart industries? With rapid technological developments and ever-greater automation andinformation available, the HRM function needs to focus on non-routine andcomplex, evidence-based and science-inspired, and creative and value-addedprofessionally demanding tasks.